Numerical Simulation of Temperature Field Evolution and Distribution Range During Movement of Underground Coal Gasification Working Face - Wei Li; Jian Liu; Lin Xin; Wei Li; Jianguo Fan; Xianmin Wang; Yan Ma; Weimin Cheng; Jiancai Sui; Maofei Niu (Energies)
Studying temperature evolution and distribution range during underground coal gasification is essential to optimize process efficiency, ensure safe and stable operation and reduce environmental impact. In this paper, based on the Liyan Coal Mine underground gasification project, the moving grid setting is used to simulate the moving heat transfer process of the underground coal gasification (UCG) flame working face (FWF). The results showed that the temperature distribution within the coal wall facing the flame is relatively narrow and remains concentrated within a limited range. Temperature distribution curves for T = 100 °C and T = 600 °C initially exhibit a nonlinear increase, reaching a maximum value, followed by a nonlinear decrease, ultimately trending towards a constant value. The maximum temperature influence ranges at ∆T = 10 °C (T = 30 °C) in the roof, left coal pillar, and floor are approximately 13.0 m, 9.0 m, and 10.1 m, respectively. The temperature values at the +1 m and +2 m positions on the roof exhibit a parabolic pattern, with the height and width of the temperature curve gradually increasing. By the end of the operation at t = 190 d, the length range of temperatures exceeding 600 °C at the +1 m position is 73 m, with a maximum temperature of approximately 825 °C, while at the +2 m position it is 31 m, with a maximum temperature of approximately 686 °C.